Pt−Co Alloy Nanoparticles on a γ‐Al2O3 Support: The Synergistic Effect between Isolated Electron‐Rich Pt and Co for Automotive Exhaust Purification. Issue 5 (8th April 2019) - Sato, Katsutoshi; Ito, Ayano; Tomonaga, Hiroyuki; Kanematsu, Homare; Wada, Yuichiro; Asakura, Hiroyuki; Hosokawa, Saburo; Tanaka, Tsunehiro; Toriyama, Takaaki; Yamamoto, Tomokazu; Matsumura, Syo; Nagaoka, Katsutoshi
Abstract: Invited for this month's cover is the group of Dr. Katsutoshi Sato and Prof. Dr. Katsutoshi Nagaoka (Kyoto University) and collaborators at Oita and Kyushu Universities. The cover picture shows the proposed mechanism for automotive exhaust purification over a Pt–Co alloy nanoparticle catalyst with an extremely low Pt/Co molar ratio. In the catalyst, the isolated electron‐rich Pt atoms are present on the surface of the nanoparticles and play an important role in NO x capture and activation, which are important elementary steps in exhaust purification. Read the full text of the article at10.1002/cplu.201800542 . Abstract : "We proposed a novel strategy that will help to lower the use of platinum‐group metal resources in supported metal catalysts used for exhaust purification." Read more about the story behind the cover in the Cover Profile and about the research itself (DOI:10.1002/cplu.201800542 ).